Plasma HIV-1 Tropism and the Risk of Short-Term Clinical Progression to AIDS or Death. - Maria Casadellà; Alessandro Cozzi-Lepri; Andrew Phillips; Marc Noguera-Julian; Markus Bickel; Dalibor Sedlacek; Kai Zilmer; Bonaventura Clotet; Jens D Lundgren; Roger Paredes; EuroSIDA in EuroCOORD (PLoS ONE, 2017)
OBJECTIVE To investigate if plasma HIV-1 tropism testing could identify subjects at higher risk for clinical progression and death in routine clinical management. DESIGN Nested case-control study within the EuroSIDA cohort. METHODS Cases were subjects with AIDS or who died from any cause, with a plasma sample with HIV-1 RNA >1000 copies/mL available for tropism testing 3 to 12 months prior to the event. At least 1 control matched for age, HIV-1 RNA and HCV status at the time of sampling were selected per each case. Conditional logistic regression was used to investigate exposures associated with clinical progression to AIDS or death. A linear mixed model with random intercept was used to compare CD4+T-cell slopes by HIV tropism over the 12 months following the date of sampling. RESULTS The study included 266 subjects, 100 cases and 166 controls; one quarter had X4 HIV; 26% were ART-naïve. Baseline factors independently associated with clinical progression or death were female gender (OR = 2.13 vs. male, 95CI = 1.04, 4.36), p = 0.038), CD4+T-cell count (OR = 0.90 (95CI = 0.80, 1.00) per 100 cells/mm3 higher, p = 0.058), being on ART (OR = 2.72 vs. being off-ART (95CI = 1.15, 6.41), p = 0.022) and calendar year of sample [OR = 0.84 (95CI = 0.77, 0.91) per more recent year, p<0.001). Baseline tropism was not associated with the risk of clinical progression or death. CD4+T-cell slopes did not differ within or between tropism groups. CONCLUSIONS The predictive role of plasma tropism determined using 454 sequencing in the context of people receiving cART with detectable VL is not helpful to identify subjects at higher risk for clinical progression to AIDS or death.